2011
DOI: 10.1016/j.jvir.2011.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Painful Pathologic Fracture of the Humerus: Percutaneous Osteoplasty With Bone Marrow Nails Under Hybrid Computed Tomography and Fluoroscopic Guidance

Abstract: A case of a 75-year-old patient with a painful pathologic humeral shaft fracture, with unacceptably high surgical risk and unsatisfactory analgesia is reported. In this case, impaired arm function and persistent pain with conservative management resulted in a poor quality of life. Palliation with image-guided percutaneous osteoplasty was considered. Because of potential cement leakage, inadequate fracture reduction, the site of the fracture, and the mobility of the joints in that area, image-guided percutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The use of cement-filled catheter has been reported [4,5]. Anselmetti et al [7] described a percutaneous osteoplasty technique using metallic tunnelers designed for central venous catheter placement. Kelekis et al [6] performed augmented cementoplasty of the humerus using a combination of microneedles and bone cement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cement-filled catheter has been reported [4,5]. Anselmetti et al [7] described a percutaneous osteoplasty technique using metallic tunnelers designed for central venous catheter placement. Kelekis et al [6] performed augmented cementoplasty of the humerus using a combination of microneedles and bone cement.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous cementoplasty is a minimally invasive alternative for patients with malignant humeral fracture unsuitable for surgery, but polymethyl methacrylate (PMMA) resists poorly to torsional forces and shear stress and is considered less effective for treating long bone tumors, with an increased risk of secondary fractures [2,3]. Various strategies have been proposed to increase the resistance of PMMA in humeral fractures, but these studies are limited to case-reports [4][5][6][7]. The present study describes a procedure of percutaneous reinforced cementoplasty (RC) for humeral pathological fractures using intralesional spindles based on a technique described in the cervico-trochanteric region [8].…”
mentioning
confidence: 99%
“…Physical and chemical properties of cement injected alone into osteolytic lesions can provide mechanical resistance to axial compressive forces, but less so to tension and torques stresses (16-18). Hence, several techniques for bone metastases were reported that included the use of cemented screws, nails, catheters and metallic mesh (19)(20)(21)(22)(23). Additionally, some studies showed feasibility and effectiveness for the treatment of painful bone metastases with kyphoplasty, radiofrequency thermal ablationor microwave ablation and cementoplasty (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the patients rate their pain score as 7 and 8 (82.61%) while 17.39% patients rated their pain score as 6. Severe pain is usually reported in pathologic fractures of the humerus [18][19][20] . As pathologic fractures were excluded from the present study, hence there was no case with severe pain intensity in present study.…”
Section: Discussionmentioning
confidence: 99%